Algunos comentarios respecto del sistema leibniziano de creencias - Moya Bedoya, Juan Diego (2013)
This paper is an exposition concerning G. W Leibniz's conceptual framework.It is an exposition of the german philosopher'sontological principies, foundation of the correspondent system of beliefs.